2019
DOI: 10.3892/etm.2019.7980
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of unilateral transverse process‑pedicle and bilateral puncture techniques in percutaneous kyphoplasty for Kummell disease

Abstract: In the present study, the efficacy of unilateral transverse process-pedicle and bilateral puncture techniques in percutaneous kyphoplasty (PKP) for Kummell disease was compared. Between March 2015 and June 2017, 63 patients with Kummell disease were recruited and underwent PKP with two different puncture techniques: A total of 38 patients were treated by unilateral transverse process-pedicle PKP and 25 patients were treated by bilateral PKP. The operative time, intra-operative fluoroscopy time, volume of bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and partially restore the height of the vertebra and correct the kyphosis [11,[22][23][24][25][26][27][28][29]. During spinal flexion and extension, due to the presence of IVC and the formation of pseudojoint, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures with bone cement in the fractured vertebrae, the height of the vertebrae was partially restored and kyphosis deformity was partially corrected, and the abnormal activity of the fractured vertebrae was eliminated, which was an important reason for pain relief [2]. Previous studies have found that PVP can effectively relieve low back pain of Kümmell's disease and OVCFs, and partially restore vertebral height and correct kyphosis [2,[23][24][25][26][27][28][29][30]. The ODI and VAS scores in both Kümmell's disease and OVCFs groups decreased after PVP treatment, but the mean score in Kümmell's disease group was higher than that in OVCFs groups [31].…”
Section: Resultsmentioning
confidence: 99%